Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
P = 2( L + W )
-divide both sides by 2
P/2 = L + W
-subtract L from both sides
P/2 - L = W
or
(P - L) / 2 = W
-divide both sides by 2
P/2 = L + W
-subtract L from both sides
P/2 - L = W
or
(P - L) / 2 = W
Hello,
We know that if we make the same operation on both sides, we don't affect the equation:
For example:
[tex]2=2 \\ 2\bold{+2}=2\bold{+2} \\ 4=4[/tex]
Do you see? we add 2 on both sides and we don't affect the equality
We can do the same with the multiplication, for example
4=4 (i'll multiply both sides by 1/2)
[tex]4*\bold{ \frac{1}{2}}=4*\bold{ \frac{1}{2}} \\ 2=2[/tex]
Now, we do exactly the same in your excercise:
[tex]P=2(L+W) \,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,[multiply\,\,by\,\,1/2] \\ \\ P*\bold{ \frac{1}{2}}=2(L+W)*\bold{ \frac{1}{2}} \\ \\ \frac{P}{2}=L+W\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,[Subtract\,\,L]\\ \\ \frac{P}{2}-\bold{L}=L+W-\bold{L}\\ \\ \frac{P}{2}-\bold{L}=L-\bold{L}+W \\ \\ \frac{P}{2}-L=W\\ \\ \boxed{ W= \frac{P}{2}-L }[/tex]
We know that if we make the same operation on both sides, we don't affect the equation:
For example:
[tex]2=2 \\ 2\bold{+2}=2\bold{+2} \\ 4=4[/tex]
Do you see? we add 2 on both sides and we don't affect the equality
We can do the same with the multiplication, for example
4=4 (i'll multiply both sides by 1/2)
[tex]4*\bold{ \frac{1}{2}}=4*\bold{ \frac{1}{2}} \\ 2=2[/tex]
Now, we do exactly the same in your excercise:
[tex]P=2(L+W) \,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,[multiply\,\,by\,\,1/2] \\ \\ P*\bold{ \frac{1}{2}}=2(L+W)*\bold{ \frac{1}{2}} \\ \\ \frac{P}{2}=L+W\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,[Subtract\,\,L]\\ \\ \frac{P}{2}-\bold{L}=L+W-\bold{L}\\ \\ \frac{P}{2}-\bold{L}=L-\bold{L}+W \\ \\ \frac{P}{2}-L=W\\ \\ \boxed{ W= \frac{P}{2}-L }[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.